A NOVEL COGNITIVE AGENT SYSTEM TO RETRIEVE RELEVANT CODE COMPONENTS FROM A REPOSITORY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Despite its well-recognized benefits, software reuse has not met its expected success due to technical, cognitive, and social difficulties. We have systematically analyzed the reuse problem (especially the cognitive and social difficulties faced by software developers who reuse) from a multidimensional perspective, drawing on our long-term research on information retrieval, human-computer interaction, and knowledge-based systems. Based on this analysis, we propose the concept of reuse-conducive development environments, which encourage and enable software developers to reuse through the smooth integration of reuse repository systems and development environments.